HEAT OF FORMATION OF PETALITE, LIALSI4O10 - Faszhauer D.W.; Cemic L. (My University, 2001)
The enthalpy of formation of petalite, LiAlSi4O10, has been measured using high-temperature solution calorimetry. The measurements were carried out in a Calvet-type twin micro calorimeter at 728°C. A 2PbO · B2O3 melt was used as a solvent. Tabulated heats of formation of the components and tabulated heat capacities of the reactants and the product (Robie and Hemingway 1995) were used to calculate the standard heat of formation of petalite from the measured heats of solution. The calculations yielded a mean value of Δf H pet298.15=−4872±5.4 kJ mol−1. This value may be compared to the heat of formation of Δf H pet298.15= −4886.5±6.3 kJ mol−1 determined by the HF solution calorimetry by Bennington et al. (1980). Faßhauer et al. (1998) combined thermodynamic data with phase-equilibrium results to obtain best-fit thermodynamic results using the Bayes method, in order to derive an internally consistent dataset for phases in the NaAlSiO4– LiAlSiO4–Al2O3–SiO2–H2O system. They determined −4865.6 ± 0.8 kJ mol−1 as the enthalpy of formation of petalite, a value that is appreciably closer to the enthalpy found in this work.
Keywords: ENTHALPY OF FORMATION; PETALITE; HIGH-TEMPERATURE SOLUTION CALORIMETRY